Mapping the obstacles to brownfield redevelopment adoption in developing economies: Pakistani Perspective. (February 2020) - Ahmad, Naveed; Zhu, Yuming; Hongli, Lin; Karamat, Jawad; Waqas, Muhammad; Taskheer Mumtaz, Syed Muhammad
Highlights: Brownfield redevelopment is confronting challenges in its implementation in developing countries. Literature on obstacles to brownfield redevelopment is compiled, and a framework is proposed to explore the important obstacles in Pakistan. Lack of capital and cost consideration were extracted as major obstacles to brownfield redevelopment in Pakistan. Lack of collaboration between the local and federal government, and lack of environmental law awareness are the second most critical barriers to BR adoption in Pakistan. Implementation and guidelines were proposed to overcome the obstacles. Abstract: Brownfields located in urban centers are potential resources for urban development projects. In developed economies, brownfield redevelopment (BR) is considered an effective strategy and an important instrument in urban planning. However, BR in developing counties, especially Pakistan, has not received the same attention due to different obstacles, and it is still in its infancy. Therefore, the objective of this study is to identify the obstacles to BR adoption in Pakistan through a review of previous studies and to analyze these obstacles through expert opinion. After an extensive literature review, this study develops a contextual relationship-based model using an integrated methodology of Interpretive Structural Modeling (ISM) and MICMAC (cross-impact matrix multiplication applied to classiﬁcation) analysis. The results of ISM outlined ownership constraints, public protests, lack of transparent communication among stakeholders, and lack of environmental justice as dependent obstacles. However, financial constraints including lack of capital and cost consideration were identified as independent obstacles and the most critical ones. The results of this study can be a stepping stone to overcome obstacles to BR and promote urban sustainability. Considerable incentives and subsidies will foster BR implementation resulting in the integration of sustainable urban development in Pakistan.